PENERAPAN MEDIA BUSY BOOK UNTUK MELATIH KREATIVITAS DAN BAHASA ANAK DI TK ASSALAM DESA TANJUNG DAYANG SELATAN - Muharrahman; Arrochman, Ichromsyah; Arum Fajriati, Dewi (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
In the learning process in Early Childhood Education requires tools that support the learning process in various teaching aids, such as media or other aids. The media used in the learning process must be able to bring children into their world so that they can motivate children in the ongoing teaching and learning process in the classroom. Initial observations at the Assalam Kindergarten in Tanjung Dayang Selatan Village indicated that the use of the media there was less effective in the learning process. The purpose of the research conducted at Assalam Kindergarten in Tanjung Dayang Selatan Village was to find out the results of the application of busy book media to train and develop creativity and language for children aged 3-5 years. This research is a qualitative descriptive research (field research) using data collection techniques in the form of observation, interviews and documentation. Using data validity test techniques and triangulation techniques, then using data analysis techniques in the form of data reduction, data display and data inference. The results of the research conducted, namely: first, busy book media can increase and stimulate children's curiosity by entertaining, encouraging motor skills, skills, mental and emotional so that busy books become effective media to introduce or test children's knowledge through game. Second, for children's language development, namely the addition of children's vocabulary increases. Based on this, the busy book media as a learning medium in increasing creativity and language for children aged 3-5 years is very effective.